Spatial and qualitative criteria for government shelters and their response to displacement during emergencies in the Gaza Strip - Al- Tarshawi, Etimad A.; El Mougher, Mohammed M.; El Agha, Mohamed R. (Journal of Risk and Crisis Management, 2019)
This study aimed at to indicate the extent to which the government shelters in the Gaza Strip responded to internal displacement according to the spatial and qualitative standards of the shelters during the Israeli military attacks on the Gaza Strip in 2014. More over to the subsequent assessment and rehabilitation of human resources and rehabilitation Public schools to be fit for shelter and protection. To achieve the goals, the study adopted the analytical descriptive approach that analyses the content of the quality and spatial standards used by the shelters, The study used various tools, including conducting Interviews with relevant persons from the Ministry of Social Development and the literature review issued by the humanitarian and shelter sectors. The study concluded a number of results, the most important of which: the readiness of the government agencies to shelter was not at the required level because of the high numbers of displaced people than expected. Also the rehabilitation processes after 2014 better than before and took into account the criteria and qualitative indicators, and recommended the study of the need to coordinate of civil and humanitarian institutions to meet human and humanitarian needs and to preserve the dignity of displaced persons.